Psychometric properties of the Brief Symptom Inventory in a clinical and nonclinical sample - Blazhevska Stoilkovska, Biljana; Naumova, Katerina (Faculty of Philosophy, Skopje, 2020)
The aim of this study is to investigate the proposed factor structure, reliability, and discriminant validity of the Macedonian translation of one of the most widely used screening and outcome measures. Both samples are drawn from two separate data sets. The clinical sample (N = 149, 57% female) is composed of outpatients formally diagnosed by psychiatrists and participants using or in need of mental health services diagnosed by psychologists through a structured diagnostic clinical interview. All diagnoses were made in adherence to ICD-10 criteria. The nonclinical sample (N = 180, 55% female) is composed of participants not meeting diagnostic criteria for any mental disorder or not needing/using mental health services in the previous six months. Confirmatory factor analysis was applied to examine the construct validity of the BSI. The results supported the original nine-factor structure in both samples, demonstrating acceptable model fit. Internal consistency of the overall BSI was high. Discriminant validity was explored by comparing the clinical and nonclinical sample on nine symptom dimensions and three global psychological distress indices. As found, the BSI differentiates between the two groups with respect to all dimensions and global indices. The study results indicate good psychometric properties of the BSI in Macedonian context.
Keywords: Brief Symptom Inventory, factorial structure, discriminant validity